2023
DOI: 10.1007/s00127-023-02447-7
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood cohesion, loneliness and perceived social isolation prior and during the COVID-19 pandemic. Longitudinal evidence from the German Ageing Survey

Abstract: Purpose To investigate the longitudinal association between neighbourhood cohesion and loneliness as well as perceived social isolation prior and during the COVID-19 pandemic (stratified by sex). Methods Longitudinal data were taken from a nationally representative sample (German Ageing Survey) of inhabitants aged 40 years and over in Germany prior (wave 6: year 2017) and during the COVID-19 pandemic (wave 8: November 2020 until February 2021; n = 6688 obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This aligns with prior research based on Swedish individuals aged 82 years and over and applying longitudinal data 37 . More severe functional impairment may particularly reflect a higher need for long‐term care ‐ and a decreased likelihood of participation in several life domains (e.g., social activities) 38 . Functional impairment can also reduce satisfaction in marital partnerships (or friendships) 38 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This aligns with prior research based on Swedish individuals aged 82 years and over and applying longitudinal data 37 . More severe functional impairment may particularly reflect a higher need for long‐term care ‐ and a decreased likelihood of participation in several life domains (e.g., social activities) 38 . Functional impairment can also reduce satisfaction in marital partnerships (or friendships) 38 .…”
Section: Discussionsupporting
confidence: 81%
“…With regard to sex‐stratified regressions, it should be noted that decreases in social network size were significantly associated with increases in depressive symptoms and decreases in life satisfaction in women, but not in men, in our study. Prior research has already demonstrated the key role of social networks for women (e.g., 39 ). Gender differences have also been reported in a recent study among individuals aged 80 and over in China using longitudinal data 40 —and also based on community‐dwelling individuals aged 85 and over residing in Tokyo (longitudinal data) 41 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 It may be worth noting that being single was particularly strongly related to the odds of being institutionalized among men. It could be that male singles in this age bracket are more dependent on institutionalized forms of housing due to differences in the social network 23,24 with women reporting stronger social ties. 24 Corresponding social networks among single women in this age bracket could in turn facilitate private forms of care -which should be investigated in future research.…”
Section: Variablesmentioning
confidence: 99%